If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(1 + 6x) = 14 + -1x (1 * -1 + 6x * -1) = 14 + -1x (-1 + -6x) = 14 + -1x Solving -1 + -6x = 14 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1 + -6x + x = 14 + -1x + x Combine like terms: -6x + x = -5x -1 + -5x = 14 + -1x + x Combine like terms: -1x + x = 0 -1 + -5x = 14 + 0 -1 + -5x = 14 Add '1' to each side of the equation. -1 + 1 + -5x = 14 + 1 Combine like terms: -1 + 1 = 0 0 + -5x = 14 + 1 -5x = 14 + 1 Combine like terms: 14 + 1 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| ln(8-6x)-2ln(x)=ln(2) | | 25-18+4(-2)= | | 3-4q=10q+100 | | W+1-5=2w | | 3x^15*x-36=0 | | 5x^2-27x+10=0 | | 7=x/2+5 | | 5y-3(y-2)+3= | | Q=xy-xy^2 | | 5+2x=3(2x+4)-5(x-2) | | 10-4(2w+1)=6w-4(6+w) | | -38=2k | | m+3n=7n | | 5(n+2)=3/5(5+10n) | | 7+3(3-2x)=7x+3(3x-2) | | 12=a-(-18) | | y^3+2y^2=0 | | -(7xy-10)+3(6xy+4)= | | -9/2(x+1)=3 | | 5x+3x^2-2x^3=0 | | 3=n-(-6) | | 0.5b+4=2+3d-0.5 | | 2(-8x+5)+5x=7(x+4) | | -6x+3(3x+12)=18 | | v+(-6)=-24 | | 3x-16+3x=2+6x-18 | | .07x+.05(x-2400)=196 | | -6y-4=-5y-7 | | 2x+3(x-1)=4x-17+2x | | 12t=9(t-15) | | 10.60+106= | | r^4=1024 |